2023
DOI: 10.3390/jcm12020509
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Human Cochlea Using an Image Analysis Tool

Abstract: Understanding cochlear anatomy is crucial for developing less traumatic electrode arrays and insertion guidance for cochlear implantation. The human cochlea shows considerable variability in size and morphology. This study analyses 1000+ clinical temporal bone CT images using a web-based image analysis tool. Cochlear size and shape parameters were obtained to determine population statistics and perform regression and correlation analysis. The analysis revealed that cochlear morphology follows Gaussian distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…The largest available electrodes (0.52 mm diameter), 59 assuming a circular apical tip, would only occupy 27% of the area in the average ST cross section and 43% in the smallest cochlea. The findings from this current study align with previous findings by Biedron et al ., 56 where histological sectioning was used but limited to 45° incremental measurements; findings by Avci et al ., 16 where μCT was used but measurements could not be conducted past 720°; and with Hussain et al ., 60 who found a ST diameter of 0.64 mm at 720° despite the technical limitations of the underlying model beyond the basal turn 24 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The largest available electrodes (0.52 mm diameter), 59 assuming a circular apical tip, would only occupy 27% of the area in the average ST cross section and 43% in the smallest cochlea. The findings from this current study align with previous findings by Biedron et al ., 56 where histological sectioning was used but limited to 45° incremental measurements; findings by Avci et al ., 16 where μCT was used but measurements could not be conducted past 720°; and with Hussain et al ., 60 who found a ST diameter of 0.64 mm at 720° despite the technical limitations of the underlying model beyond the basal turn 24 …”
Section: Discussionsupporting
confidence: 91%
“…The largest available electrodes (0.52 mm diameter), 59 assuming a circular apical tip, would only occupy 27% of the area in the average ST cross section and 43% in the smallest cochlea. The findings from this current study align with previous findings by Biedron et al, 56 where histological sectioning was used but limited to 45 incremental measurements; findings by Avci et al, 16 where μCT was used but measurements could not be conducted past 720 ; and with Hussain et al, 60 who found a ST diameter of 0.64 mm at 720 despite the technical limitations of the underlying model beyond the basal turn. 24 The typical electrode tip diameters for the major CI electrode manufacturers include Advanced Bionics HiFocus™ Mid-Scala arrays with an apical diameter of 0.52 mm 59 , Cochlear™ Nucleus ® CI422 Slim Straight arrays with an apical diameter of 0.3 mm 29 , MED-EL FLEXSOFT arrays with an apical minor axis of 0.4 mm 30 , and Oticon Medical EVO ® arrays with a 0.4 mm 31 apical diameter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For comparison with human studies, the relative standard deviation (RSD) was calculated. Our data showed a volume variability of 14.7% RSD with a total mean volume of 5.3 ± 0.78 μL, comparable studies in humans showed a volume variability between 6.3% RSD (Hussain et al, 2023) to 20% RSD (Dhanasingh et al, 2021). To determine the cochlear "footprint, " the parameters A and B were assessed.…”
Section: Discussionsupporting
confidence: 75%